Wykorzystanie strukturalnej miary rozwoju oraz mierników European Innovation Scoreboard do pomiaru innowacyjności regionalnej - Strahl, Danuta (The Application of Structural Measure of Development and the European Innovation Scoreboard Determinants for Measuring Regional Innovation, 2007)
The article presents the procedure of regional innovation measurement as an attempt to quantify the multidimensional phenomenon and takes into consideration as follows:- information resources of the European Union statistics - the European Innovation Scoreboard,- aggregate measures applying both local and global pattern in the process of variable values normalization. The suggested procedure of regional innovation measurement refers to the following stages:a) establishing partial indices of regional innovation based on the European Innovation Scoreboard,b) establishing modified indices:- local (country level) index of regional innovation,- global (European) index of regional innovation,c) classification of regions based on regional innovation indices,d) establishing structural measure of regional innovation. In the presented proposal of regional innovation measurement the following informations, in five thematic groups, divided into two zones - INPUT and OUTPUT were used in the European Innovation Scoreboard:INPUT:1) factors stimulating innovation,2) knowledge creation,3) innovation and entrepreneurship.OUTPUT:4)innovation application,5) intellectual property.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (18); 2007; nr 1151, s. 77-88